2006
DOI: 10.1021/bi060027g
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Induced Toxicity Is Associated with Platinum Deposition in Mouse Kidney Mitochondria in Vivo and with Selective Inactivation of the α-Ketoglutarate Dehydrogenase Complex in LLC-PK1 Cells

Abstract: The anti-cancer drug cisplatin is nephrotoxic and neurotoxic. Previous data support the hypothesis that cisplatin is bioactivated to a nephrotoxicant. The final step in the proposed bioactivation is the formation of a platinum-cysteine S-conjugate followed by a pyridoxal 5'-phosphate (PLP)-dependent cysteine S-conjugate β-lyase reaction. This reaction would generate pyruvate, ammonium and a highly reactive platinum (Pt)-thiol compound in vivo that would bind to proteins. In the present work, the cellular locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 68 publications
5
36
0
Order By: Relevance
“…The present study indicates that cisplatin itself binds to mitochondrial GOT. A study by Zhang et al 39) confirms our results. They found that a pyridoxal 5-phosphate-dependent cysteine S-conjugated GOT reaction formed a platinum-cysteine S-conjugate of cisplatin.…”
Section: Discussionsupporting
confidence: 91%
“…The present study indicates that cisplatin itself binds to mitochondrial GOT. A study by Zhang et al 39) confirms our results. They found that a pyridoxal 5-phosphate-dependent cysteine S-conjugated GOT reaction formed a platinum-cysteine S-conjugate of cisplatin.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, male and female laboratory cats aged 1-3 years (3.1 ± 0.3 kg) and male beagle dogs aged 2-3 years (12.5 ± 0.8 kg) were selected from among non-treated or control animals (n = 5-6) in other projects. Since the mitochondrial AST was reported to catalyze the bioactivation of cisplatin and to transfect into renal cells (Zhang et al, 2006), this enzyme was selected among the C-S lyases. The mitochondrial AST activity was measured by a previously reported method (Cooper and Meister 1985) with some modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The Pt-cysteine S-conjugates are reabsorbed via renal cysteine heterodimetric amino acid transporters into the proximal tubular epithelia, where they are metabolized by C-S lyase to produce toxic reactive metabolites (Hanigan and Devarajan 2003;Townsend et al 2003;Townsend and Hanigan 2002;Zhang et al 2006;Zhang and Hanigan 2003).…”
Section: Cisplatin Conjugates With Reduced Glutathione (Gsh) Cysteinmentioning
confidence: 99%
“…It is worth noting that GDH in brain supplies 2-oxoglutarate for its oxidation, which occurs through the 2-oxoglutarate dehydrogenase complex (OGDHC), forming a supramolecular structure with GDH which in turn binds aspartate aminotransferase [189,190]. Since OGDHC dysfunction is also associated with neurodegeneration [191,192], the importance of GDH in the development of neurodegenerative processes may be mediated by impaired 2-oxoglutarate supply to OGDHC.…”
Section: Medical Significance Of Gdhmentioning
confidence: 99%